Analysis of mechanical properties and forces produced by transpalatal bars made from low-nickel alloy - Matheus M. Pithon; Rogério L. dos Santos; Ana Maria Bolognese; Eduardo Franzotti Sant´anna; Margareth Maria Gomes de Souza (Universidade Estadual de Campinas, 2015)
Aim: This study evaluated assess the mechanical properties and forces produced by transpalatal bars made from low-nickel alloy. Methods: Using a template, a single operator made all transpalatal bars from 0.032" and 0.036" wires of two different alloys, thus originating four groups, namely: A8 (0.032" conventional stainless steel), B8 (0.032" low-nickel stainless steel), A9 (0.036" conventional stainless steel), and B9 (0.036" low-nickel stainless steel). The bars were then activated and mounted onto a device developed to serve as a support for mechanical assay in a universal testing machine (Emic DL 10.000). The values of resilience and ductility were obtained using the Origin 8 software. Results: No statistically significant differences (P > 0.05) were observed between Groups A8 and B8 neither between A9 and B9 for 0.5-, 1.0-, and 5-mm deformations. However, statistically significant differences (P < 0.05) were found in all groups for 15-mm deformation. Groups B8 and B9 showed greater ductility and resilience compared to groups A8 and A9, respectively. Conclusions: Low-nickel stainless steel transpalatal bars release the same amount of force for activations less than 10 mm compared to those made from conventional stainless steel. Mechanically, the low-nickel stainless steel bars are more ductile and resilient.